Binge Eating, Body Image Dissatisfaction And Anxiety Among Female Adolescents In Malaysia - Liew, Jia Xian (2024)
Binge eating involves consuming an overwhelmingly large proportion of food in a short duration of time accompanied by a sense of subjective loss of control. Since a young age, humans form perceptions about their bodies and internalise negative evaluation of one’s body which leads to body image dissatisfaction (bid) that occurs most frequently during adolescence and is more common among females. Bid is suggested to be the onset of disordered eating behaviours including binge eating. Studies have shown that anxiety symptoms are high among individuals with binge eating overall as they binge eat to reduce “bad moods” or negative affect. However, research also demonstrates that the process of binge eating is associated with a reduction in anxiety, particularly among individuals with binge eating disorder. Anxiety may thus serve as a risk for binge eating. Meanwhile, the after effects of binge eating may further create more anxiety which then again compel the anxiety-reducing behaviour of binge eating. Thus, individuals who binge eat seem to be in a vicious downward spiral of anxiety. This study compared the prevalence of binge eating between 16-year-old girls from two types of public schools in malaysia, national schools, and chinese-medium schools. Additionally, this study identified the role of anxiety in the relationship between bid and binge eating. A total of 396 participants completed self-reports assessing body satisfaction (dissatisfaction), binge eating symptoms, anxiety and disordered eating. They also reported heights and weights. There was no significant difference in binge eating scores between students from the two types of schools.